Idade de início de obesidade, apego e níveis de organização de personalidade em pacientes candidatos a cirurgia bariátrica - Bergmann, Carolina Goldman (2020)
BACKGROUND: Candidates for bariatric surgery are an important group for the study of personality, in order to predict possible complications and poor results in the postoperative period. Psychodynamic aspects of personality interfere in adaptive processes. Therefore, psychiatric evaluation by specialized teams is essential before bariatric surgery. Difficulties in parental bonding have been identified as one of the predisposing factors for obesity. The way in which parents offer care and protection is important in developing the ability to deal with adverse situations in adulthood. However, currently there are no studies that associate personality characteristics with the age of onset of obesity in bariatric patients. OBJECTIVES: to investigate how levels of personality organization, parental bonding and age of onset of obesity are related in obese patients seeking care at the COMPUCRS clinic. METHODS: A retrospective, cross-sectional, observational, descriptive study, with case-control was conducted. Information was collected from medical records attended at COMPUCRS from July 2016 to December 2018. Data from 475 patients were analyzed, with clinical, demographics and PBI and IPO-Br’s scores. RESULTS: Regarding the PBI, low father care was found to be significantly more frequent in the group with late onset of obesity (46.7% versus 57.0%; p = 0.040). In addition, in relation to the IPO-Br, there was a statistically significant difference for PGP above the cut-off point, which was more frequent in the group with late onset of obesity (13.6% versus 21.6%; p = 0.032). CONCLUSION: The findings of this study demonstrate that individuals with alterations in parental bonding and levels of personality organization may need more in-depth psychotherapeutic interventions to achieve better results of bariatric surgery.